Calculation of Critical Temperatures by Empirical Formulae - Trzaska, J. (Archives of metallurgy and materials, 2016)
The paper presents formulas used to calculate critical temperatures of structural steels. Equations that allow calculating temperatures Ac , Ac , Ms and B were elaborated based on the chemical composition of steel. To elaborate the equations the multiple regression method was used. Particular attention was paid to the collection of experimental data which was required to calculate regression coefficients, including preparation of data for calculation. The empirical data set included more than 500 chemical compositions of structural steel and has been prepared based on information available in literature on the subject.